2016
DOI: 10.1038/srep25482
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Transcription of Interferon-stimulated Genes by TNF-α and IFN-α Augments Antiviral Activity against HCV and HEV

Abstract: IFN-α has been used for decades to treat chronic hepatitis B and C, and as an off-label treatment for some cases of hepatitis E virus (HEV) infection. TNF-α is another important cytokine involved in inflammatory disease, which can interact with interferon signaling. Because interferon-stimulated genes (ISGs) are the ultimate antiviral effectors of the interferon signaling, this study aimed to understand the regulation of ISG transcription and the antiviral activity by IFN-α and TNF-α. In this study, treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 39 publications
1
63
0
Order By: Relevance
“…Nuclear factor-kappa B (NF-B) signaling participates in modulating the activation of various proinflammatory cytokine genes and ISGs (20), contributing to a vital role in combating pathogen invasion. By using Huh7 and Caco-2 cell-based NF-B luciferase reporter cells, we further excluded the activation of the NF-B pathway by TZD (see the supplemental material).…”
Section: Irf-1 Inhibited Hunv Replication and Contributed To The Tzd-mentioning
confidence: 99%
“…Nuclear factor-kappa B (NF-B) signaling participates in modulating the activation of various proinflammatory cytokine genes and ISGs (20), contributing to a vital role in combating pathogen invasion. By using Huh7 and Caco-2 cell-based NF-B luciferase reporter cells, we further excluded the activation of the NF-B pathway by TZD (see the supplemental material).…”
Section: Irf-1 Inhibited Hunv Replication and Contributed To The Tzd-mentioning
confidence: 99%
“…Studies have shown that type I IFN treatment induces degradation of IB␣, increasing NF-B p65/p50-mediated transcription of antiviral ISGs, such as Mx1 and Nmi (8). Moreover, different groups have provided evidence that type I IFNs and TNF-␣ work together to protect the host from lethal virus infection by enhancing transcription of antiviral ISGs through activation of both JAK/STAT and NF-B signaling pathways (19,30). Interestingly, our data suggest that Slfn2 plays a key role in the regulation/balance of type I IFN-mediated activation of STAT1 and NF-B.…”
Section: Discussionmentioning
confidence: 99%
“…4). Studies have shown that IFN-␤ induces activation of NF-B through both canonical and noncanonical pathways and that the promoter regions of ISGs have binding sites for NF-B (9,19). Accordingly, we next investigated the role of Slfn2 in type I IFN-induced activation of the NF-B signaling pathway.…”
Section: Absence Of Slfn2 Expression Enhances Ifn-␤-inducible Transcrmentioning
confidence: 99%
“…TNF-α plays several therapeutic roles within the body, including immunostimulation, resistance to tumors, and sleep regulation2650. TNF-α is also an important mediator of resistance against infectious diseases225152535455. For example, in experimental leishmaniasis, insufficient TNF-α is associated with progressive disease and death53.…”
Section: Discussionmentioning
confidence: 99%